Ibn âArabi and the Transcendental Unity of Religions - Bahri, Media Zainul (Al-Jamiah Research Centre, 2012)
This essay describes Ibn âArabiâs comprehensive views, captured in his important Futuhat and Fusus, on the concept of wahdat al-adyan, the discrepancy of beliefs, and the Shariâah as well as its juncture and its unity. Elaborated explanation in this paper is expected to result in a true understanding of this crucial issue, particularly the concept of religious pluralism in the discourse of Islamic studies. Ibn Arabiâ extensively Â discusses religion in the sense of the âidealâ versus âhistoricalâ or âesotericâ versus âthe exotericâ. Ibn âArabi concludes that the absolute unity of religions may only occur within spiritual, ideal, or transcendental realm (or âesotericâ), which is beyond the formal form of religions. Hence, the transcendental unity of religions cannot be found in the formal form of religions nor in the shariâah.[Artikel ini mengulas pandangan Ibn âArabiâ mengenai wahdat al-adyan seperti dijelaskan dalam dua bukunya; Futuhat dan Fusus, dan perbedaan dan kesamaan antara iman dan shariah. Diharapkan diskusi artikel ini berkontribusi dalam kajian pluralisme, utamanya dalam disiplin studi Islam. Dalam diskusinya, Ibn Arabiâ Â menjelaskan perbedaan âidealâ dan âhistorikalâ atau antara âesoterikâ dan âeksoterikâ. Ibn âArabi berpendapat bahwa kemanunggalan agama-agama dapat dicapai melalui spiritualitas, ideal, atau dimensi transcendental (esoterik) yang ada di luar tampilan formal agama-agama. Dengan kata lain, kemanunggalan tersebut tidak akan ditemukan pada shariâah.]